Tomb Inscription of Ptolemaios of Tlos - (:unkn) unknown (SUNA & INAN KIRAC RESEARCH INST MEDITERRANEAN CIVILIZATIONS, 2011)
Tomb Inscription of Ptolemaios of Tlos The article presents a tomb inscription in the private collection of Necati Binici who bought it in 2001 in Fethiye, Mugla. As there is no information regarding its provenance recorded in the inventory book, it is not possible to say anything precise about its finds-pot. However, as the owner of the inscription is of nos, it may have been found in the vicinity of that city. The first six lines of the inscription are engraved with bigger letters and give the name of Neoptolemos, who had this tomb built, his father Ptolemaios for whom the tomb was built, and his natural father's and his adopted father's names; it is highly likely that this part was given emphasis. Based on the letter characteristics this inscription can be dated to the 1(st)-2(nd) centuries AD. Scientific importance of this inscription comes from the first-time documentation of the word (sic) in the ninth line and the word (sic) in the 14(th) line. This term related with land management is not known from other published documents, therefore, we are not able to give detailed information, but the word seems to have derived from the verb (sic), meaning to rent products. It is known from an another inscription that Licinnius Musaios of Pinara in Lycia, a land-owner ((sic)), was honored with a tomb altar by his (sic) Zosimos. Here, (sic) should be the tenant who collected the products in return for the (sic) on behalf of the land-owner. On the other hand (sic) means the value of the rent paid in kind and is mentioned in land renting documents of the Ptolemaic or Roman Imperial Egypt. When this rent is paid in cash, which was very rare, then it was called (sic). One of the duties of the (sic) mentioned in this inscription must have been to collect the amounts of rent in kind on behalf of the land-owner. However, this term can only be clarified when other epigraphic material with similar terminology are found. Translation of the inscription is as follows: Neoptolemos (had this tomb altar built) for his father Ptolemaios of Tlos, adopted son of Apollonios, son of Neoptolemos. Neoptolemos or his tenant who rented the field together with its produce, will burn the meat piece of a castrated goat or the sacrificed animal's shoulder, valuing 15 denarii as a sacrifice, and offer baked pastry every year at the necropolis. In case the tenant does not commit (the offerings), then he will have sinned against the deities of the underground.